The evaluation and enhancement strategies of core competencies for older adult caregivers in integrated medical and older adult care institutions - Rong, Chao; Wu, Qun-Hong; Xu, Hong-Yan; Chang, Ming; Zhang, Lan; Xie, Rong-Rong (Frontiers in Public Health, 2024)
The study aimed to understand the main skills of elderly caregivers and find ways to improve these skills. We selected participants using a method called random cluster sampling, where caregivers from 17 different medical and nursing care facilities across seven districts in Hangzhou were chosen. We collected 492 valid questionnaires and conducted interviews with 150 people. To analyze the data, we used T-tests and Analysis of Variance (ANOVA) to identify what factors affect caregivers' skills. We also performed multiple regression analysis to explore these factors in more depth. The analysis showed that age(P=0.041), annual income(P<0.001), and having a training certificate(P<0.001) significantly influence the skills of elderly caregivers. Specifically, caregivers' age and whether they had a training certificate were linked to how competent they were, with income being a very strong factor. The study highlighted a gap between the caregivers' current skills and the skills needed for high-quality care. This gap shows the need for training programs that are specifically tailored to the caregivers' diverse needs and cultural backgrounds. Medical and eldercare facilities should adjust their work and educational programs accordingly. It's also important to look at how caregivers are paid to make sure their salary reflects their skills and the quality of care they provide. Finally, it's crucial to integrate a comprehensive training program that leads to certification within eldercare organizations.